Temporal Variability of Thermohaline Fine-Structure Associated With the Subtropical Front Off the Southeast Coast of New Zealand in High-Frequency Short-Streamer Multi-Channel Seismic Data - Cooper, Joanna K.; Gorman, Andrew R.; Bowman, M. Hamish; Smith, Robert O. (Frontiers in Marine Science, 2021)
Seismic oceanography generally makes use of multi-channel seismic reflection data sourced by air gun arrays and long hydrophone streamers to image oceanographic water masses and processes—often piggybacking on surveys that target deeper geological features below the seafloor. However, due to the acquisition methods employed, shallow (upper 200 m or so) regions of the ocean can be poorly imaged with this technique, and resolution is often lower than desirable for imaging fine-structure within the water column. In 2012, we collected a set of higher-resolution seismic lines off the southeast coast of New Zealand, with a generator-injector airgun source and hydrophone streamer configuration designed to improve images of shallower water masses and their boundaries. The seismic lines were acquired with coincident expendable bathythermograph deployments which provides direct ties between physical oceanographic data and seismic data, allowing for definitive identification of the Subtropical Front and associated water masses in the subsurface. Repeat acquisition along the same transect shows significant temporal variability on the scale of hours, illustrating the highly dynamic nature of this important ocean boundary. Comparisons to conventional low-frequency seismic data in the same location show the value of high-resolution acquisition methods in imaging the near-surface of the ocean and allowing subsurface features to be linked to their expressions at the surface.